Use of the Fenton Reaction as a Pretreatment of Elephant Grass and Its Effect on Enzymatic Hydrolysis - Godinho, Emmanuel Zullo [UNESP]; Hasan, Salah Din Mahmud; Baumgartner, Tatiana Rodrigues da Silva; Kaminski, Thiago Spinardi; Candelaria, Murilo Henrique Hernandez; Silveira, Flávia Taguti; Reginato, Marco Antonio (Springer Nature, 2022)
The objective of this work was to test the Fenton reaction on pretreatment of elephant grass aiming the results of cellulose increase and the delignification process. A subsequent study of the enzymatic hydrolysis of the pretreated elephant grass and the mathematical modeling of hydrolysis was performed. A Doehlert-type experimental design was used into the pretreatment stage and the best results were obtained at the central point with an average of 53.80% of cellulose and 10.00% of lignin. The enzymatic hydrolysis of pretreated grass with Fenton reaction was performed, with a commercial enzyme, where the best yield (17.39%) of reducing sugars was obtained with 20 g L−1 of enzyme in 72 h and higher productivity (2.51 g L−1 h−1) observed in 2 h. It was possible to adjust the proposed mathematical model to the hydrolysis process. It was observed that, for higher concentrations of enzyme, the proposed mathematical model adjusts better the experimental results (R2 = 0.993). It can be observed with these results that there was an increment in the economic profitability of the enzymatic hydrolysis process due to the relation of the operational parameters, so that it can be used in new projects and industrial applications.
Keywords: Cellulose and lignin; Enzymatic kinetics; Ethanol production; Fenton reaction